Dataset on absorption spectra and bulb concentration of phenolic compounds that may interfere with onion pyruvate determinations - Beretta, Hebe Vanesa (2017)
We present data on absorption spectra (400–540 nm) and concentration of phenolic compounds quercetin, myricetin, kaempferol, rutin, catechin, epicatechin gallate (ECG) and epigallocatechin gallate (EGCG), in yellow, red and white onions. These data are related to the article entitled “Variability in spectrophotometric pyruvate analyses for predicting onion pungency and nutraceutical value” (Beretta et al., 2017) [1]. Given the relevance of pyruvate determinations for estimating onion pungency and functional value, it is important to identify compounds that can interfere with pyruvate determinations when using two previously published analytical procedures, namely Schwimmer and Weston (1961) (SW) [2] and Anthon and Barret (2002) (AB) [3], which are based on spectrophotometry and light-absorbance at 420 nm and 515 nm, respectively. The data presented in this article are absorption spectra for 7 onion phenolic compounds in the range 400–540 nm, which include wavelengths used by the two pyruvate analytical methods (Schwimmer and Weston, 1961; Anthon and Barret, 2002) [2,3] that were compared in our reference article (Beretta et al., 2017) [1]. Additionally, bulb content data for these 7 phenolic compounds in onion cultivars and F2 progenies with different bulb color were included to allow further analyses.